The dynamic change of serotype distribution and antimicrobial resistance of pneumococcal isolates since PCV13 administration and COVID-19 control in Urumqi, China - Guo, Meng-Yang; Shi, Xing-Hai; Gao, Wei; Tian, Ju-Ling; Yuan, Lin; Yang, Juan; Wumaier, Dilinuer; Cao, Jiang; Abulimiti, Reziwaguli; Zhang, Wen-Li; Yao, Kai-Hu (Frontiers in Cellular and Infection Microbiology, 2023)
Objective This study aims to analyze the serotype distribution and drug resistance of Streptococcus pneumoniae isolated from children aged 8 days to 7 years in Urumqi, China, between 2014 to 2021, during which PCV13 was introduced in the private sector’s immunization program and COVID-19 control was administrated in the last 2 years. Methods Serotypes of S. pneumoniae isolates were determined by Quellung reaction, and their susceptibility against 14 antimicrobials were tested. According to the start year of PCV13 administration (2017) and COVID-19 control (2020), the study period was divided into three stages: 2014–2015, 2018–2019, and 2020–2021. Results A total of 317 isolates were involved in this study. The most common serotypes were type 19F (34.4%), followed by 19A (15.8%), 23F (11.7%), 6B (11.4%), and 6A(5.0%). The coverage rate of both PCV13 and PCV15 was 83.0%. The coverage of PCV20 was a little higher at 85.2%. The resistance rate against penicillin was 28.6% according to the breakpoints of oral penicillin, which would reach up to 91.8% based on the breakpoints of parenteral penicillin for meningitis. The resistance rates to erythromycin, clindamycin, tetracycline, and sulfamethoxazole-trimethoprim were 95.9%, 90.2%, 88.9%, and 78.8%, respectively. The PCV13 isolate was more resistant to penicillin than the non-PCV13 ones. There was not any significant change found in the serotype distribution since the PCV13 introduction and the COVID-19 control. The resistance rate against oral penicillin slightly elevated to 34.5% in 2018–2019 from 30.7% in 2014–2015 and then decreased significantly to 18.1% in 2020–2021 (χ2 = 7.716, P < 0.05), while the resistance rate to ceftriaxone (non-meningitis) continuously declined from 16.0% in 2014–2015 to 1.4% in 2018–2019 and 0% in 2020–2021 (Fisher = 24.463, P < 0.01). Conclusion The common serotypes of S. pneumoniae isolated from children in Urumqi were types 19F, 19A, 23F, 6B, and 6A, which we found to have no marked change since the PCV13 introduction and the COVID-19 control However, the resistance rate to oral penicillin and ceftriaxone significantly declined in the COVID-19 control stage.